Significance of total Leucocyte Count in the diagnosis of acute appendicitis in children - Arshad Kamal; Shafiullah (Gomal Journal of Medical Sciences, 2010)
Background: Clinical presentation of acute appendicitis in children is usually not typical and needs supportive laboratory tests. The aim of this study was to evaluate the significance of total leucocyte count in the diagnosis of acute appendicitis in children.